Bone Scintigraphic Pattern and Correlation with Serum Prostate Specific Antigen Levels in Prostate Cancer Patients at NINMAS - Ananna, Farzana Rahman; Islam, Urnas; Parveen, Rahima; Reza, Sharmin; Adnan, Sheikh Md; Bailey, Shamsun Nahar; Sultana, Nasreen (Bangladesh Journal of Nuclear Medicine, 2024)
Abstract not available Bangladesh J. Nuclear Med. 27(1): 56-61, 2024